THE NOTES ABOUT SOME BASE PROPERTIES OF FUNCTIONS - MASAROVA, Renata (Trends in education, 2011)
The article describes posible techniques of defining monotone, possibly convex and concave functions. It points out the most repeated errors and erroneous notion, which are made by students of technical schools. It includes posible extension of this area too.
Keywords: monotone function; increasing convex funkction.